Analysis of Trip Attraction Models in Morotai CBD (Central Business District) - Fitro Darwis; Anggriyawan Djafar; Elfira Resti Mulya (Universitas Khairun, 2022)
The development of an area in land use can increase along with the increase in population in Morotai Island Regency, including the Morotai CBD area. In terms of urban transportation systems, generation and attraction have an important role in defining the development of a city, region, or area. The purpose of this research is to analyze of trip attraction modeling in the CBD area of Morotai. The concept of trip attraction modeling is analyzed using regression analysis, with various independent variables. The modeling analysis was carried out with the help of SPSS software using Stepwise multiple linear analysis methods. The results of the study show that the factors that influence the attraction of vehicle in the Morotai CBD area are : the number of visitors (X4), the ratio of visitors against the building area (X10), the ratio of employees against the number of rooms (X13), the number of rooms(X5), the ratio of employees against the building area (X11), as well as the ratio of employees against the number of rooms(X12). And from the results of linear regression analysis, the best transport attraction model was found to be Y 1 = 86.790 + 0.422X 4 – 558.735X 10 + 1.949X 13 for the motorcycle (SM) attraction model and Y 2 = 12.183 + 0.091X 5 – 26.265X 11 + 0.292X 12 for the light vehicle (KR) model.